Study to compare the effectiveness of intravaginal misoprostol alone with combined use of intravaginal misoprostol and intracervical foley’s catheter for termination of mid trimester pregnancy - Mahajan, Puneeta; Sharma, Neeraj; Sharma, Parwati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The main concern of obstetrician is to provide the most effective and safest regimen for mid trimester termination of pregnancy which combines the shortest expulsion interval with least side effects. The combination of intravaginal misoprostol and intracervical Foley catheter for second trimester pregnancy termination has been described in previous studies with conflicting results. Hence gap exists in literature and not adequate evidence available so this study is undertaken. Methods: A prospective and interventional randomized comparative study was conducted in the department of obstetrics and gynecology, tertiary care centre, New Delhi. A total 60 pregnant female of 14 to 20 weeks of gestation who were admitted for termination of pregnancy due to any indication included in the study. Patients were divided into two groups (30 patients in each group). Group A (misoprostol and foleys combination group) and Group B (misoprostol group). Quantitative variables were compared with unpaired t-test/Mann-whitney test (when the data sets were not normally distributed) between the two groups and qualitative variables were compared by using chi-square test/Fisher’s exact test. Results: The mean induction to abortion interval was 18.31±1.95 hours in the female where misoprostol and foleys combination was used and 21.90±2.62 hours in the women where misoprostol alone used group. Authors found a significant reduction in induction to expulsion time in misoprostol and foleys combination group as compared to misoprostol alone group for mid-trimester termination of pregnancy. Total required dose of misoprostol use for termination of pregnancy was significantly less (p 0.008) in the women where both misoprostol and foleys was used than misoprostol alone. Conclusions: With the use of intracervical Foley’s catheter, the duration from induction to expulsion of abortus gets shortened and required dose of misoprostol is also reduced without any significant increase of side effects.